QIRA’AT AL-QUR’AN - Moh Abd Azis; Andi Muhammad Akbar (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Al-Qur'an is Kalamullah who was sent down to the Prophet Muhammad. through the angel Gabriel as. and read it including worship. In understanding the Al-Qur'an, there are various readings of the Al-Qur'an, the term is better known as the Qiraat Al-Qur'an. This Qiraat Al-Qur'an has existed since it was revealed to the Prophet Muhammad in Mecca. However, this qira'at began to be used when the Prophet was already in Medina. When delivering the revelations he had received, the prophet always used readings in accordance with the abilities of the companions who were present at that time. So that the ability of a friend to read the Al-Qur'an also varies, depending on how many kinds of readings (qira'at) he has received from the Prophet. As a result, the variety of qira'at that developed in each region experienced differences. After the Prophet's death, the companions became more active in spreading the Qur'an by establishing madrassas in the vicinity of where they lived. So, it is not surprising that after the generation of friends, there emerged qira'at experts among the tabi'in.